The IMPACT OF THE KOMAPE JUDGMENT ON THE SOUTH AFRICAN COMMON LAW OF DELICT: AN ANALYTICAL REVIEW Komape v Minister of Basic Education [2020] 1 All SA 651 (SCA); 2020 (2) SA 347 (SCA) - Buthelezi, Michael Celumusa (Obiter, 2022)
In a rare case where the State is mulcted with delictual damages for failure to discharge their constitutional obligations to provide infrastructure in public schools, such as adequate sanitation facilities, the Supreme Court of Appeal awarded damages for emotional shock to the parents and siblings of a Grade-R learner who had drown in a pit-toilet. At the same time, the Court refused to develop the Constitution, 1996, to award separate damages for pure grief and bereavement not accompanied by serious psychological lesions, as well as constitutional damages. The judgment has been widely welcomed by children rights activities and is regarded as heralding a new era in holding the State (education officials) accountable for failure to fulfill their constitutional obligations towards learners, especially regarding the eradication of pit latrines in public schools. This note gives an analytical review of the judgment and is impact on the (development of) the common law delict, in particular, in the area of emotional shock and psychological injury. In the process, the case note specifically takes interest in the rationality for the SCA’s rejection of the Appellants’ argument for the development of the common law to award damages for a pure grief and bereavement (in addition to damages for emotional shock and psychological lesions) and constitutional damages. In the end, the case note concurs with the Court that it was unnecessary in the circumstances of the case to develop the common law. In fact, it is asserted in this note that the common law delict of emotional shock, in its current form, adequately compensate victims. Therefore, the SCA was right to reject the argument to develop the common law, as well as the awarding of constitutional damages.